2021
DOI: 10.1055/s-0041-1734573
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caffeine Consumption on Autologous Full-Thickness Skin Graft Healing in an Animal Model

Abstract: Background There exists contradictory evidence that states both the beneficial and deleterious effects of caffeine on wound healing. The general population might unknowingly consume caffeine that negatively affects wound healing. The main objective of this study is to investigate the effect of daily caffeine consumption on wound healing, specifically full-thickness skin graft (FTSG). Methods Forty Sprague-Dawley rats were randomized into four groups of equal size: control-dose (CD), low-dose (LD), me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The effect of caffeine on animal subjects, such as rats, showed abnormal microscopic findings: increased keratinization and disorganization of the epidermal cells, and epidermal and dermal atrophy, which leads to a reduction in skin thickness and may be a risk factor for inducing skin atrophy [127]. Increased collagen synthesis was observed in subjects who received caffeine and its daily consumption affects full-thickness skin graft healing [128]. Also, it was demonstrated that taurine reduces oxygen radicals, promotes angiogenesis and collagen synthesis, and inhibits neutrophil infiltration in the muscle flaps during ischemia and reperfusion.…”
Section: Long-term Studies On Animalsmentioning
confidence: 99%
“…The effect of caffeine on animal subjects, such as rats, showed abnormal microscopic findings: increased keratinization and disorganization of the epidermal cells, and epidermal and dermal atrophy, which leads to a reduction in skin thickness and may be a risk factor for inducing skin atrophy [127]. Increased collagen synthesis was observed in subjects who received caffeine and its daily consumption affects full-thickness skin graft healing [128]. Also, it was demonstrated that taurine reduces oxygen radicals, promotes angiogenesis and collagen synthesis, and inhibits neutrophil infiltration in the muscle flaps during ischemia and reperfusion.…”
Section: Long-term Studies On Animalsmentioning
confidence: 99%